New test system for identification of Aerococcus, Enterococcus, and Streptococcus species. - You, M S (1986)
A total of 244 strains of Aerococcus, Enterococcus, and Streptococcus species were tested by the RapID STR system (Innovative Diagnostic Systems Inc., Atlanta, Ga.) for identification. Strains were identified without additional tests or with additional conventional tests suggested by the IDS compendium manual. Our data indicate that the RapID STR system identifies 89% of the beta-hemolytic Streptococcus species if serological procedures are used in conjunction with the rapid physiological procedures. Of the group D streptococci, 98% of the Enterococcus species and 100% of the group D non-Enterococcus species were correctly identified. Of the commonly occurring viridans group Streptococcus species, 93% were correctly identified, and 79% of the less frequently occurring viridans group Streptococcus species were correctly identified. All of the Streptococcus pneumoniae and Aerococcus strains tested were correctly identified.